2011
DOI: 10.1007/s10693-011-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Opaque Bank Activities, and Risk/Return Efficiency: Pre- and Post-Crisis Evidence from Turkey

Abstract: Does better corporate governance unambiguously improve the risk/return efficiency of banks? Or does either a re-orientation of banks' revenue mix towards more opaque products, an economic downturn, or tighter supervision create off-setting or reinforcing effects? The authors relate bank efficiency to shortfalls from a stochastic risk/return frontier. They analyze how internal governance mechanisms (CEO duality, board experience, political connections, and education profile) and external governance mechanisms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Studies in this category mostly explored the direct or moderating effects of board configurations, that is, duality or role separation on firms' financial outcomes using four key sets of measurements, such as return on assets and return on equity (Duru, Iyengar, & Zampelli, 2016; Gaur, Bathula, & Singh, 2015; Hadani, Dahan, & Doh, 2015; Krause et al, 2019; Naseem, Lin, Rehman, Ahmad, & Ali, 2019; Peng, Zhang, & Li, 2007; Pi & Timme, 1993; Ramdani & Witteloostuijn, 2010; Rechner & Dalton, 1991; Syriopoulos & Tsatsaronis, 2012), Tobin's Q (Elsayed, 2007; Jermias & Gani, 2014; Mínguez‐Vera & Martín‐Ugedo, 2010; Poutziouris, Savva, & Hadjielias, 2015; S. Singh, Tabassum, Darwish, & Batsakis, 2018), IPO underpricing or withdrawal (Chahine & Tohmé, 2009; Helbing, Lucey, & Vigne, 2019; Lin & Chuang, 2011), and financial performance in terms of investments and diversifications (Kim et al, 2009; Lim, 2015; Lim & McCann, 2013; D. Singh & Delios, 2017). The majority of these studies agreed that CEO duality is negatively related to firm financial performance (Duru et al, 2016; Grove, Patelli, Victoravich, & Xu, 2011; Jermias & Gani, 2014; Judge, Naoumova, & Koutzevol, 2003; Kaymak & Bektas, 2008; Naseem et al, 2019; Pi & Timme, 1993; Sanan, Jaisinghani, & Yadav, 2019; Schepker et al, 2018) and argued that role separation can facilitate better financial outcomes for companies (de Jonghe, Disli, & Schoors, 2012; De Maere et al, 2014; Li & Naughton, 2007; Rechner & Dalton, 1991; Stockmans, Lybaert, & Voordeckers, 2013; Syriopoulos & Tsatsaronis, 2012). Some also noticed that the presence of a dual CEO–chair can have detrimental effects on firm financial performance through inefficient investments (Aktas et al, 2019; Kim et al, 2009; cf.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in this category mostly explored the direct or moderating effects of board configurations, that is, duality or role separation on firms' financial outcomes using four key sets of measurements, such as return on assets and return on equity (Duru, Iyengar, & Zampelli, 2016; Gaur, Bathula, & Singh, 2015; Hadani, Dahan, & Doh, 2015; Krause et al, 2019; Naseem, Lin, Rehman, Ahmad, & Ali, 2019; Peng, Zhang, & Li, 2007; Pi & Timme, 1993; Ramdani & Witteloostuijn, 2010; Rechner & Dalton, 1991; Syriopoulos & Tsatsaronis, 2012), Tobin's Q (Elsayed, 2007; Jermias & Gani, 2014; Mínguez‐Vera & Martín‐Ugedo, 2010; Poutziouris, Savva, & Hadjielias, 2015; S. Singh, Tabassum, Darwish, & Batsakis, 2018), IPO underpricing or withdrawal (Chahine & Tohmé, 2009; Helbing, Lucey, & Vigne, 2019; Lin & Chuang, 2011), and financial performance in terms of investments and diversifications (Kim et al, 2009; Lim, 2015; Lim & McCann, 2013; D. Singh & Delios, 2017). The majority of these studies agreed that CEO duality is negatively related to firm financial performance (Duru et al, 2016; Grove, Patelli, Victoravich, & Xu, 2011; Jermias & Gani, 2014; Judge, Naoumova, & Koutzevol, 2003; Kaymak & Bektas, 2008; Naseem et al, 2019; Pi & Timme, 1993; Sanan, Jaisinghani, & Yadav, 2019; Schepker et al, 2018) and argued that role separation can facilitate better financial outcomes for companies (de Jonghe, Disli, & Schoors, 2012; De Maere et al, 2014; Li & Naughton, 2007; Rechner & Dalton, 1991; Stockmans, Lybaert, & Voordeckers, 2013; Syriopoulos & Tsatsaronis, 2012). Some also noticed that the presence of a dual CEO–chair can have detrimental effects on firm financial performance through inefficient investments (Aktas et al, 2019; Kim et al, 2009; cf.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…For example, the study of Kim et al (2009) argued that the presence of large institutional owners could be beneficial to mitigating the power imbalance between CEO duality and the rest of the board, which will eventually restrict investments in unrelated industries. Delgado-García et al (2010) suggested that many institutional investors might, given their short-term orientation, have a negative impact on company reputation. One possible explanation for such dilemmas is found in Lin and Chuang (2011), who studied an emerging economy and argued that, although institutional ownership can improve the monitoring of firm managers in the case of principal-agency conflicts, it can have opposite implications when a principal-principal conflict exists.…”
Section: Institutional Ownershipmentioning
confidence: 99%
“…However, Keeton (1999) argues that an increase in loan growth is likely to lead to higher NPL only if the source of faster loan growth is due to a shift in bank credit supply. Therefore, the most plausible explanation for this disconnect is the conservative lending stance adopted by Turkish banks after the severe banking crisis in 2001 and the subsequent policy measures taken by the government to seriously deal with their NPL problems (see, e.g., Tanyeri, 2010;De Jonghe et al, 2012). The coefficient estimates on the error corrections terms suggests that SME lending and non-performing SME loans are related to each other in the long run.…”
Section: Baseline Panel Causality Testmentioning
confidence: 99%
“…In addition, in our analysis we account for the regulatory mandates with the introduction of the Sarbanes‐Oxley Act (SOX) in 2002 as a dummy, which takes the value of 0 if year is 2000–2001 and the value of 1 otherwise consistent with Pathan and Faff () . We also impose a crisis dummy, which takes the value of 1 if year is 2007–2010 and zero otherwise in order to account for the financial crisis period (Pathan and Faff, ; De Jonghe et al., ). Finally, in order to capture the market risk we use the Volatility Implied Index indicator (VIX) .…”
Section: Data and Preliminary Analysismentioning
confidence: 99%